Faktor-Faktor yang Mempengaruhi Kepatuhan Penggunaan Alat Pelindung Diri (APD) pada Pekerja Konstruksi : Kajian Sistematis Literatur - Tengku Siti Neza Azmarina; Andriyani Andriyani; Triana Srisantyorini (Lembaga Pengembangan Kinerja Dosen, 2025)
Personal Protective Equipment (PPE) is an important aspect for workers in various fields, and it is the responbility of companies to ensure safety in the workplace. This research uses the systematic Literature Review (SLR) method by first selecting journals or studies, then obtaining results in the form of references from ideas or models that will be developed in the future. The research is conducted from January to April 2025. Through this method, an assessment of the impact of PPE usage on the rate of work accidents, which remains relatively high in various aspects, can be carried out. The results of the data analysis showed a significant positive influence of safety culture on compliance in the use of personal protective equipment (PPE). However, it cannot be ignored that there are still many standard operating procedures (SOPs) that are not running well, so the risks for workers remain.